(Table S1) Age determination of sediment cores of the Ontong Java Plateau - Jennifer Fehrenbacher; Pamela Martin (PANGAEA, 2011)
We present a reconstruction of deep-water carbonate saturation state (Delta [CO3]2-) in the western equatorial Pacific for the Last Glacial Maximum (LGM) and deglaciation based on changes in the Mg/Ca ratio of planktic foraminifers with increased water depth. Our data suggest there have been changes in bottom waterDelta [CO3]2- over the past 25,000 years at water depths as shallow as 1.6 km. The Delta [CO3]2- reconstruction for the LGM suggests Delta [CO3]2- was similar or slightly higher than modern values between 1.6 and 2.0 km, shifting sharply to lower values (an average ~30 μmol/kg lower) below 2.5 km. The shift in chemistry between 2.0 and 2.5 km supports a hypothesis that Pacific overturning circulation occurred deeper during the LGM with a slightly more ventilated water mass above 2.0 km. The data are not consistent with enhanced preservation in this region of the deep Pacific at depths greater than 2.5 km, suggesting that the long-held view of better preservation throughout the glacial deep Pacific must be reevaluated. For the deglaciation, we have evidence of a Delta [CO3]2- maximum that suggests enhanced deglacial preservation between 1.6 and 4.0 km in comparison to the Holocene and the LGM. The deglacial Delta [CO3]2- was as much as 28 μmol/kg higher than modern between 1.6 and 4.0 km. Results suggest carbonate burial rates were 1.5 times greater during the deglacial than the over the past 5 kyr.
Supplement to: Fehrenbacher, J; Martin, P (2011): Western equatorial Pacific deep water carbonate chemistry during the Last Glacial Maximum and deglaciation: Using planktic foraminiferal Mg/Ca to reconstruct sea surface temperature and seafloor dissolution. Paleoceanography, 26(2), PA2225, https://doi.org/10.1029/2010PA002035